"HLA-G 3′UTR gene polymorphisms and rheumatic heart disease: a familial study among South Indian population". Issue 1 (December 2017) - Poomarimuthu, Maheshkumar; Elango, Sivakumar; Soundrapandian, Sambath; Mariakuttikan, Jayalakshmi
Abstract Background Rheumatic heart disease (RHD) is an autoimmune disease where cross reactive CD4+ T cells are involved in the pathogenesis of valvular damage. Human Leukocyte Antigen-G (HLA-G), an immunosuppressive molecule playing a crucial role in the inhibition of T cell response is associated with the pathogenesis of various autoimmune and inflammatory diseases. Genetic polymorphisms within the 3′untranslated region (UTR) of HLA-G influences its expression and thus disease pathogenesis. Hence, the present study aims to unravel the association of 14 bp Ins/Del (rs66554220) and +3142 C/ G (rs1063320) polymorphisms in 3′ UTR of HLA-G with RHD. Methods This familial study consists of 99 RHD families (99 RHD patients, 140 parents and 126 healthy siblings). The 14 bp Ins/Del and +3142 C/ G polymorphisms were evaluated by PCR using sequence specific primers and its transmission disequilibrium (TD) was tested by TD test in 70 trio families. Results The frequency of +3142 C/C genotype was high in patients with combined valvular lesions (CVL) (OR = 5.88; pc = 0.012) and pooled RHD patients (P: OR = 2.76;p = 0.043; pc = 0.076) when compared to healthy siblings. Under the additive (OR = 5.50; pc = 0.026) and recessive genetic model (OR = 5.88; pc = 0.012), the +3142 C/C genotype was significantly associated with CVL in patients. Conclusion The results suggest that the +3142 C/C genotype may be associated with minor risk for the development of RHD and is more likely to influence the severity of the disease.